Prevalence of neurotic and stress-related disorders among volunteers during wartime: predictors of development and formation - Sumariuk, Богдан; Yurtsenyuk, Ольга (Psychosomatic Medicine and General Practice, 2024)
Relevance. russia's full-scale invasion of Ukraine poses significant challenges to the mental health of Ukrainians. Special attention must be given to first responders, who are directly involved in providing assistance in conflict zones or working with individuals exposed to severe stressors. This category also includes volunteers who are actively engaged in delivering psychosocial and humanitarian aid. Volunteering during the war in Ukraine is associated with high levels of distress, constant changes in work environments, emotional burnout, and direct exposure to both individual and collective trauma. These factors place volunteers at increased risk for developing neurotic and stress-related disorders. Thanks to volunteer initiatives, Ukraine was able to mitigate many socio-economic challenges during the early stages of the war. However, as the scope of volunteer tasks expands, so do stress levels and exhaustion, which negatively impact productivity and efficiency. This highlights the need for research into the factors contributing to the onset and spread of mental health disorders among volunteers. Aims. To investigate the causes and prevalence of neurotic and stress-related disorders among individuals engaged in volunteer work during the war. Materials and methods. The study consisted of two phases and included both quantitative and qualitative data analysis. The first phase involved identifying predictors of the development and vulnerability to neurotic and stress-related disorders among volunteers providing aid during the war. This was done using a standardized evaluation questionnaire that included psychodiagnostic tools, a socio-demographic data survey, and mental health status complaints. The second phase involved diagnostic verification of mental disorders among volunteers who received positive screening results based on the psychodiagnostic methods. The study sample comprised 288 volunteers engaged in humanitarian aid during the Russo-Ukrainian war. The sample included individuals aged 18 to 60 with varying levels of volunteer experience. Results. Statistical analysis of the personalized questionnaire for volunteers during the war revealed that the main factors contributing to the development of neurotic and stress-related disorders are: feelings of hopelessness (39.2% of respondents); inability to adapt to new environments (58.3%); difficulty in assimilating new norms and rules (55.8%); separation or divorce from a loved one (43.3%); worsening of living conditions (65%); forced career change (23.3%); negative influence of the media (42.3%); interpersonal conflicts within the volunteer group (34.3%); and feelings of isolation from others (21.1%). Out of the total of 288 volunteer respondents, 114 participants from the first phase of the study were selected for clinical-psychopathological interviews, representing 39.58% of the total sample. Following the interviews, it was determined that 82 out of 114 participants met the diagnostic criteria for neurotic or stress-related disorders according to ICD-10, specifically from the F40-F48 section on “Neurotic, stress-related, and somatoform disorders.” The remaining 32 volunteers did not meet the criteria for mental disorders. Conclusions. The study revealed that volunteer activities in wartime conditions are associated with an increased risk of developing neurotic and stress-related disorders. To reduce this risk, it is essential to implement psychological support systems for volunteers and raise their awareness of their own mental health. Additionally, it is recommended to develop personalized psychological correction programs, especially for those who have been involved in humanitarian activities for extended periods.